2016
DOI: 10.1002/lary.26051
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal ultrasound and vocal fold movement in the pediatric cardiovascular intensive care unit

Abstract: 3b. Laryngoscope, 127:167-172, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 38 publications
(98 reference statements)
1
107
0
Order By: Relevance
“…Newer high‐frequency probes allow for improved resolution of small laryngeal lesions. Previous work has demonstrated that laryngeal ultrasound can be used to evaluate vocal fold mobility in neonates with much less physiologic impact compared to FNL . A limitation of LUS is resolution at the air–soft tissue interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer high‐frequency probes allow for improved resolution of small laryngeal lesions. Previous work has demonstrated that laryngeal ultrasound can be used to evaluate vocal fold mobility in neonates with much less physiologic impact compared to FNL . A limitation of LUS is resolution at the air–soft tissue interface.…”
Section: Discussionmentioning
confidence: 99%
“…4 In both adults and infants, flexible nasolaryngoscopy (FNL), with or without strobe, can be uncomfortable and cause statistically significant changes in heart rate, blood pressure, and oxygen saturation. 5,6 In addition, 25% of adults undergoing FNL have reported gagging, and 10% have dyspnea with the procedure. 7 For young children, FNL often requires two or more adults to restrain the child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a high degree of inter‐rater and intra‐rater reliability was demonstrated in a blinded study assessing US as the diagnostic technique for pediatric vocal cord paralysis . Moreover, Ongkasuwan et al have recently demonstrated that LUS is comparable to flexible nasolaryngoscopy for evaluating vocal fold mobility as well as for identifying vocal fold nodules in the pediatric population …”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, a high degree of inter-rater and intra-rater reliability was demonstrated in a blinded study assessing US as the diagnostic technique for pediatric vocal cord paralysis. 14 18,19 The value of LUS in the diagnosis of laryngomalacia in infants with congenital stridor has not been investigated. We hypothesize that LUS can accurately and reliably diagnose laryngomalacia in infants with congenital stridor in comparison to FLB and thus may replace FLB in selected cases of congenital stridor and can be used as a valuable screening method in others.…”
mentioning
confidence: 99%